GENEALOGI KUASA DAN PENGETAHUAN: DEKONSTRUKSI PERAN MADRASAH SEBAGAI INSTRUMEN HEGEMONI IDEOLOGI NEGARA PADA MASA DINASTI ABBASIYAH - Eko Ngabdul Shodikin; Sa’adi; Rahmat Hariyadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The struggle between educational institutions and political power structures is a historical phenomenon that demands a critical reading of the power-knowledge relationship within the classical Islamic civilizational tradition. This research aims to deconstruct the role of the madrasah as an instrument of state ideological hegemony during the Abbasid Dynasty. Utilizing a qualitative-historical design with a Foucauldian genealogical approach, this study uncovers how the madrasah was operated as a discursive apparatus to produce a